Thermodynamic behavior of dissolved oxygen and hydrogen in pure vanadium - Zhong, Dapeng; Pei, Guishang; Xiang, Junyi; Pan, Cheng; Gu, Wuan; Lv, Xuewei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The mechanism governing the deoxidation of vanadium metal is regarded as fundamental knowledge; however, it has not been elucidated in existing literature. In this paper, the thermodynamic data of V-H-O systems were summarized, and the Gibbs free energies of the main compounds were calculated. Consequently, the deoxidation limits of different reductants in a V-O system were evaluated, namely: Si, Al, and Mg. It was observed that Si cannot remove an O content of less than 7.27 wt% from V. However, Al was the stronger reducing agent; it could remove O contents of up to 0.01 and 0.1 wt% at 800 and 1050 °C, respectively. Nevertheless, Mg exhibited the best reducing properties as it could remove less than 0.01 wt% of O at 1100 °C. The addition of H2 renders the V-O solid solution unstable to a certain extent, thereby indicating that H2 facilitates deoxygenation. Furthermore, the results obtained by analyzing the equilibrium conditions were in accordance with the results of the deoxidation limit in the V-O system. In other words, this study demonstrates that the oxygen in vanadium can be effectively controlled by changing the reductant dosage and temperature.
Keywords: V-H-O solid solution; generating Gibbs free energy; deoxidation limit; Equilibrium phase